The Joint Dynamics of Sovereign Ratings and Government Bond Yields - Makram El-Shagi; Gregor von Schweinitz (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2015)
In the present paper, we build a bivariate semiparametric dynamic panel model to reproduce the joint dynamics of sovereign ratings and government bond yields. While the individual equations resemble Pesaran-type cointegration models, we allow for different long-run relationships in both equations, nonlinearities in the level effect of ratings, and asymmetric effects in changes of ratings and yields. We find that the interest rate equation and the rating equation imply significantly different long-run relationships. While the high persistence in both interest rates and ratings might lead to the misconception that they follow a unit root process, the joint analysis reveals that they converge slowly to a joint equilibrium. While this indicates that there is no vicious cycle driving countries into default, the persistence of ratings is high enough that a rating shock can have substantial costs. Generally, the interest rate adjusts rather quickly to the risk premium that is in line with the rating. For most ratings, this risk premium is only marginal. However, it becomes substantial when ratings are downgraded to highly speculative (a rating of B) or lower. Rating shocks that drive the rating below this threshold can increase the interest rate sharply, and for a long time. Yet, simulation studies based on our estimations show that it is highly improbable that rating agencies can be made responsible for the most dramatic spikes in interest rates.
urn:nbn:de:101:1-201505263215
Keywords: C14; C25; F34; G24; 330; sovereign risk; rating agencies; semiparametric model; nonlinearities